IMPLEMENTASI KEBIJAKAN IZIN MENDIRIKAN BANGUNAN PADA DINAS PENATAAN RUANG DAN PERUMAHAN KOTA PALU - M. Syukur, M. Syukur (Katalogis, 2015)
This research aims at finding out the causes of the ineffectiveness of the implementation of building license policy at the Department of Land Use and Housing. This is a qualitative research in terms of descriptive method. There are two kinds of data in this research, namely primary and secondary data. The techniques of the data collection are observations, interviews, documentations, and triangulation. This research uses a purposive sampling technique to obtain the informants. The data analysis used is interactive model of Miles and Huberman, consists of data reduction, data presentation, and conclusion. This research uses the theory of Van Meter and Van Horn which consists of 6 aspects, they are standard and policy objectives, resources, communications among the executives, the characteristics of the executives, social conditions, politics and economy, and the executives attitudes. Based on the result of this research, the implementation of building license policy at the Department of Land Use and Housing of Palu City is not effective yet. First: the minimum socializations cause people’s ignorance of the principles and benefits of buildings license. Second: team personnel performance of space utilization is not maximal because of lack of personnel to supervise and curb buildings. Third: the sanctions are not forceful to the offenders, so that the people are not aware and do not obey the law. Fourth: The coordination of related organizations is not maximal yet. Thus, the researcher concludes that the implementation of building license policy at Parliament is not fully maximal, because only 3 aspects are fulfilled while the others are not effective and maximal yet.